Analisis kemampuan representasi matematis peserta didik sekolah dasar ditinjau dari resiliensi matematis - Lestari, Anggita Puji; Riyadi, Riyadi; Wahyuningsih, Siti (Universitas Sebelas Maret, 2023)
This research aims to describe the mathematical representation abilities of students with high, medium and low mathematical resilience. This research is a descriptive qualitative research. The data collection techniques used were questionnaires, tests, and interviews. The data analysis technique in this research used the Miles and Huberman model which consists of data reduction, data presentation, and drawing conclusions. The results of the research concluded that: 1) Students with high mathematical resilience fulfill all indicators of mathematical representation ability in both linguistic, visual and symbolic aspects; 2) Students with moderate mathematical representation abilities meet both indicators in visual representation and do not meet indicators in language and symbolic aspects; 3) Students with low mathematical resilience, one of whom does not meet the indicators for language, visual or verbal. One of the students met one indicator, namely the verbal indicator aspect.